Geothermal reservoir potential of volcaniclastic settings: The Valley of Mexico, Central Mexico. (May 2015) - Lenhardt, Nils; Götz, Annette E.
Abstract: The geothermal potential of the Valley of Mexico has not been addressed in the past, although volcaniclastic settings in other parts of the world contain promising target reservoir formations. An outcrop analogue study of the thermophysical rock properties of the Neogene rocks within the Valley of Mexico was conducted to assess the geothermal potential of this area. Permeability and thermal conductivity are key parameters in geothermal reservoir characterization and the values gained from outcrop samples serve as a sufficient database for further assessment. The mainly low permeable lithofacies types may be operated as stimulated systems, depending on the fracture porosity in the deeper subsurface. In some areas also auto-convective thermal water circulation might be expected and direct heat use without artificial stimulation becomes reasonable. Thermophysical properties of tuffs and siliciclastic rocks qualify them as target horizons for future utilization of deep geothermal reservoirs. Highlights: Outcrop analogue study on thermophysical rock properties of Neogene rocks of the Valley of Mexico. First assessment of the geothermal potential of the Valley of Mexico. High potential of the Valley of Mexico for future geothermal reservoir utilization. Low permeable lithotypes may be operated as stimulated systems.